KONSELING ONLINE SEBAGAI UPAYA MENANGANI MASALAH PERUNDUNGAN DI KALANGAN ANAK MUDA - Anaway Irianti Mansyur; Aip Badrujaman; Rochimah Imawati; Dini Nur Fadhillah (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
The presence of technology is changing the way people to get information and communication. In the field of counseling, information technology offers some of the latest innovations to reach out, facilitate and communicate with individuals who need help from all over the world. This qualitative research collected data through literature study by analyzing 5 research results from various academics in various countries and conducting interviews with 10 youth aged 19-23 years, and 3 counselors. The results of this qualitative study indicate that online counseling makes it easy for youth in expressing the problem in their life. In addition, online counseling has great potential in offering therapy and can be done anywhere. Therefore, clients can minimize transportation costs for face-to-face counseling. Although the results of the analysis of previous studies indicate that online counseling has a weakness that is lack of knowledge and special abilities possessed by counselors in communicating through chat and lack of skills in writing texts to avoid misunderstandings with online counseling users. In the other side, previous research shows solutions related to the use of online counseling. The counselor must face the development of technology and use it as a facility to communicate with young people.